High-water-content hydrogels exhibiting superior stiffness, strength, and toughness. (May 2020) - Tran, Van Tron; Mredha, Md. Tariful Islam; Jeon, Insu
Abstract: The low mechanical properties of high-water-content hydrogels often hinder their broad use in biomedical applications, especially in replacing/treating load-bearing tissues. Inspired by the protein structure of load-bearing tissues, we developed high-water-content hydrogels with excellent mechanical properties using a hydrophobic–hydrophilic copolymer strategy employing a benzene-based amphiphilic monomer, 5-acrylamidoisophthalic acid (AAI), as the major hydrophobic component and acrylamide (AAm) as the major hydrophilic component. The AAI monomer, connected with two –COOH functional groups, allowed the hydrogel to absorb excess water via H-bonding without compromising its homogeneity and structure. The AAI-rich hard-phase regions (via benzene–benzene interactions and hydrophobic associations) and AAm-rich soft-phase regions resulted in the high-water-content ( ∼ 80 wt%) hydrogel exhibiting a combination of good mechanical properties. Graphical abstract: Highlights: High-water-content hydrogels with excellent mechanical properties were developed. A hydrophobic–hydrophilic copolymer-based strategy was adopted for the synthesis of robust hydrogels. 5-acrylamidoisophthalic acid monomers with two –COOH functional groups were employed as the hydrophobic component. Acrylamide monomers were employed as the hydrophilic component. The hydrogels were very stiff, strong, and tough, maintaining a high water content.